2014
DOI: 10.1097/mcg.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment and Management of Patients With Nonvariceal Upper Gastrointestinal Bleeding

Abstract: Upper gastrointestinal bleeding (UGIB) is a substantial clinical and economic burden, with an estimated mortality rate between 3% and 15%. The initial management starts with hemodynamic assessment and resuscitation. Blood transfusions may be needed in patients with low hemoglobin levels or massive bleeding, and patients who are anticoagulated may require administration of fresh frozen plasma. Patients with significant bleeding should be started on a proton-pump inhibitor infusion, and if there is concern for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Yet in over 80% of cases of UGIB, interventions such as endoscopic therapy, blood transfusion or surgery are not needed to stop the bleeding [ 55 ]. Although co-morbid conditions may also play a role in the need for hospitalization and other outcomes, not all patients with GIB require admission, hence the critical importance of stratifying patients into being at low or high risk for developing adverse events using validated prognostic scores [ 56 ]. A risk assessment tool that correctly identifies very low-risk patients, soon after presentation, who do not need hospital admission or intervention and can be safely discharged to obtain an elective out-patient endoscopy has the potential of reducing health resource utilization in acute UGIB [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet in over 80% of cases of UGIB, interventions such as endoscopic therapy, blood transfusion or surgery are not needed to stop the bleeding [ 55 ]. Although co-morbid conditions may also play a role in the need for hospitalization and other outcomes, not all patients with GIB require admission, hence the critical importance of stratifying patients into being at low or high risk for developing adverse events using validated prognostic scores [ 56 ]. A risk assessment tool that correctly identifies very low-risk patients, soon after presentation, who do not need hospital admission or intervention and can be safely discharged to obtain an elective out-patient endoscopy has the potential of reducing health resource utilization in acute UGIB [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though an initial analysis had suggested that tranexamic acid could possibly reduce mortality, a subsequent subgroup evaluation could not confirm this effect (40). No impact on mortality, rebleeding rate and transfusion requirements was noticed as well, and thus a formal recommendation for its use in patients with UGIB cannot be done (7).…”
Section: Pre-endoscopic Treatmentmentioning
confidence: 99%